PENGARUH PROMOSI DAN MINAT BELI JILBAB TERHADAP PENGGUNAAN APLIKASI TIKTOK SHOP PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS ISLAM TAHUN ANGKATAN 2020 UIN RADEN FATAH PALEMBANG - Novela, Elysa; Apriyanti, Winda; Maghfiroh, Lailatul (Asyafina Akademik Press, 2023)
The TikTok application is widely used for creativity to business by the public. Because of the large number ofTikTok users, the TikTok Shop feature was created to attract buyers, especially students, by doing promotions.One of the products that can be purchased on TikTok Shop is the hijab. This study aims to find out whether thereis an influence of promotion and buying interest on the use of TikTok Shop in students of the Faculty of Economicsand Islamic Business specifically for the class of 2020. This research was conducted on active students of theFaculty of Economics and Islamic Business in the class of 2020 UIN Raden Fatah Palembang. The type of researchused quantitative research, where this research is based on findings achieved using statistical data collection. Sothat the data used comes from giving a questionnaire of 250 samples that meet the creteria. From the results ofresearch on the t test, it shows that promotion and interest in buying hijab partially has a significant positive effecton the use of Tiktok Shop. In the F test, promotion and interest in buying hijab simultaneously had a significantpositive effect on the use of TikTok Shop.